eLearning Opportunities (Global Journal of Computer Science and Technology, 2012)
Both opportunities and prospects are sometimes used interchangeably however, in this paper, opportunity refers to the 2018;availability of eLearning resources and service2019; while prospects denote 2018;futuristic expectations about the role of information and communication technologies (ICTs) in higher education institutions (HEIs). The empirical findings suggest that people score lower on opportunities but significantly high on the prospects showing that they are not quite happy with the facilities and services available (due to the development, implementation and use problems 2013; or simply management problems of eLearning). But they can clearly foresee the significant role of ICTs or education technologies (ETs) in future in the context of developing countries like Pakistan. Furthermore, these differences are attributed to the demographic diversities of the respondents, meaning that the demographic variation changes the power and direction of the user-attitudes towards eLearning. This paper uses stepwise regression to gradually glean-out the most significant predictors of opportunities and prospects from a group (eight) of demographics.
Keywords: ICTS; ETS; HEIS; VLE; elearning; eteaching; epedagogy; ecourses; opportunities; prospects; demographic-attributes